2002
DOI: 10.1046/j.1365-2958.2002.02743.x
|View full text |Cite
|
Sign up to set email alerts
|

Clostridial VirR/VirS regulon involves a regulatory RNA molecule for expression of toxins

Abstract: Summary We analysed the region encoding VR‐RNA (VirR‐regulated RNA), which has been reported to be positively regulated by the two‐component VirR/VirS system in Clostridium perfringens. The VR‐RNA promoter identified by primer extension analysis was preceded by a probable VirR‐binding site (CCAGTTNNNCAC), which resembled a repeated sequence motif present in the promoter region of the theta‐toxin (pfoA) gene. A VR‐RNA‐null mutant, constructed by a homologous recombination, exhibited a reduced amount of transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
126
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(128 citation statements)
references
References 23 publications
2
126
0
Order By: Relevance
“…The plc gene encodes alpha-toxin and has been found to be indirectly regulated by the VirS-VirR system via VR-RNA (6,41). Previous in vitro binding experiments showed that VirR does not bind to this promoter region (11), as was observed in this study (Fig.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…The plc gene encodes alpha-toxin and has been found to be indirectly regulated by the VirS-VirR system via VR-RNA (6,41). Previous in vitro binding experiments showed that VirR does not bind to this promoter region (11), as was observed in this study (Fig.…”
Section: Resultssupporting
confidence: 76%
“…Two of these open reading frames, CPE0845 and CPE0920, were found to encode hypothetical proteins, while CPE0846 and hyp7 encode the protease alpha-clostripain (40) and the regulatory RNA molecule, VR-RNA (6, 41), respectively. The expression of both CPE0846 and hyp7 has been demonstrated to be VirR dependent, and it is assumed that the expression of CPE0845 and CPE0920 is regulated by VirR in a similar manner (6,40,41).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations